The Effect of Interpersonal Communication and Work Motivation on Employee Performance: A Quantitative Study at Honda Semarang Centre - Febriana, Kharisma Ayu; Rohman, Fatkhur (Social Sciences and Humanities Reviews, 2025)
Background: Employee performance is pivotal in driving organizational success, particularly in highly dynamic sectors such as the automotive industry. Within such environments, interpersonal communication and work motivation are considered essential factors influencing work outcomes. However, practical gaps often arise, leading to underperformance despite theoretically favorable conditions. Aims: This study aims to investigate the effect of interpersonal communication and work motivation on employee performance in the Body Repair Division at Honda Semarang Centre. Methods: A quantitative associative approach was employed, involving a saturated sample of all 30 employees. Data were gathered via a structured questionnaire measured on a Likert scale and analyzed using multiple linear regression. Instrument validity and reliability were confirmed, and classical assumption tests were conducted. Results: Findings reveal that both interpersonal communication and work motivation significantly and positively influence employee performance, both independently and collectively. The model’s coefficient of determination (R²) is 0.949, suggesting that 94.9% of performance variation is explained by these two variables. Descriptive statistics indicate high average scores across all variables with strong internal consistency. Conclusion: This study affirms that fostering open, empathetic, and supportive communication channels, coupled with effective motivational strategies, substantially boosts employee performance. The high explanatory power of the model underscores the strategic value of psychosocial factors in human resource management. These insights not only validate existing theories by Devito and Herzberg but also offer actionable recommendations for practice. Organizations should prioritize interpersonal engagement and incentive systems as integral components of their performance management frameworks, particularly in performance-intensive industries. Sustained investment in these areas is likely to result in improved employee satisfaction, reduced operational frictions, and enhanced organizational productivity.